Thrombo-inflammation linking androgen suppression with cardiovascular risk in patients with prostate cancer - Antonia Beitzen-Heineke; David R. Wise; Jeffrey S. Berger (Cardio-Oncology)
Abstract Androgen deprivation therapy (ADT), a key element of prostate cancer treatment, is associated with increased risk for cardiovascular morbidity and mortality. The underlying mechanisms include adverse metabolic alterations, but further mechanisms are likely. Animal studies suggest increased progression of atherosclerosis in androgen deprived conditions. Based on in vitro studies, lack of androgens may modulate immune cells including monocytes, macrophages, and T-cells towards a pro-inflammatory phenotype and pro-atherogenic function. As a novel aspect, this review summarizes existing data on the effect of androgens and androgen deprivation on platelet activity, which play a major role in inflammation and in the initiation and progression of atherosclerotic lesions. Testosterone modulates platelet aggregation responses which are affected by dose level, source of androgen, and age. Data on the effects of ADT on platelet activity and aggregation are limited and conflicting, as both increased and decreased aggregation responses during ADT have been reported. Gaps in knowledge about the mechanisms leading to increased cardiovascular risk during ADT remain and further research is warranted. Improved understanding of pathogenic pathways linking ADT to cardiovascular risk may help identify clinically useful diagnostic and prognostic biomarkers, and accelerate finding novel therapeutic targets, and thus optimize prostate cancer treatment outcomes.